2020
DOI: 10.3390/app10196833
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Rhus Verniciflua Stokes Extract Alleviates Nonalcoholic Fatty Liver through the AMPK/SREBP1/PCSK9 Pathway in HFD-Induced Nonalcoholic Fatty Liver Animal Model

Abstract: Background: We have previously reported the anti-hepatic lipogenic effect of fermented Rhus verniciflua stokes extract (FRVE) in an oleic-acid-treated HepG2 cell model. Methods: Herein, we advanced our understanding and evaluated the impact of FRVE in HFD-fed C57BL/6 mice using an animal model of nonalcoholic fatty liver disease (NAFLD). Milk thistle extract was used as a positive control to compare the effects of FRVE. Results: FRVE decreased body weight, intra-abdominal fat weight, and liver weight. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A recent study revealed that SREBF1 is activated through zinc finger and BTB domain-containing 7A (ZBTB7A), which causes lipid accumulation and progression of NAFLD [ 63 ]. Numerous studies have reported that SREBF1 is a potential target influencing NAFLD, as evidenced by administration of various interval treatments [ 64 66 ]. A recent study in 2021 by Elsayed et al indicated that SREBF1 elevation is a risk factor in the progression of NAFLD and that, following treatment of NAFLD, this gene was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that SREBF1 is activated through zinc finger and BTB domain-containing 7A (ZBTB7A), which causes lipid accumulation and progression of NAFLD [ 63 ]. Numerous studies have reported that SREBF1 is a potential target influencing NAFLD, as evidenced by administration of various interval treatments [ 64 66 ]. A recent study in 2021 by Elsayed et al indicated that SREBF1 elevation is a risk factor in the progression of NAFLD and that, following treatment of NAFLD, this gene was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are no clinical studies on liver function. Lee et al reported that FRVE has an anti-hepatic lipidemic effect by upregulating AMPK in cell and animal models [ 8 , 11 ]. In particular, they confirmed in an animal model that the levels of ALT, AST, TC, and TG decreased when animals with nonalcoholic fatty liver ingested FRVE [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that FRVE has an anti-hepatic lipidemic effect by upregulating AMPK in cell and animal models [ 8 , 11 ]. In particular, they confirmed in an animal model that the levels of ALT, AST, TC, and TG decreased when animals with nonalcoholic fatty liver ingested FRVE [ 8 ]. ALT and AST are blood indicators that increase during liver damage and are important parameters that can predict the state of liver diseases such as hepatocellular disease or hepatitis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations